Community-based rehabilitation for older adults post-stroke in Thailand: An ethnographic study - Niramol Somtua; Khanitta Nuntaboot (Belitung Nursing Journal)
Background: Stroke is a leading cause of disability among older adults, with long-term effects on their independence and quality of life. In Thailand, while previous studies have explored aspects of post-stroke rehabilitation, there remains a gap in understanding how to effectively integrate healthcare services, community resources, and cultural practices into a comprehensive, sustainable rehabilitation model.